New landscape conceptualization as a guideline for spatial development: A case study from Serbian spatial planning practice - Pihler Vladimir (University of Novi Sad, Department of Geography, Tourism and Hotel Management, 2021)
This paper is focused on clarification of the basic principles for the establishment of an innovative approach in the field of landscape research through its application in spatial planning documents in Ser-bia. The key question is: how the practice of considering landscape character could direct new spatial arrangements, based on the development of strategic spatial planning documents? The paper describes the results of analysis undertaken during the development of the "Spatial plan for a special-purpose area The Cultural Landscape of Sremski Karlovci". The landscape character assessment was the main methodology taken to define value of landscape character as the starting point for defining border of cultural landscape and "representative landscape units", as well as for guiding sustainable land use management which is opposed to the traditional approach of land-use decision making. Based on landscape character value, this research provides the elements for creating a different conceptual framework for spatial planning in Serbia which is one of the most effective model of the implementation of the European Landscape Convention.